Studies on Rheological Characteristic of Wastewater Treatment Plant (WWTP) Sludge and Process Optimization - Hong, Eugene Ewe Jinn (Curtin University, 2017)
Rheological behaviour of sludge is a function of various operational parameters. This research is aimed at investigating rheological characteristics of sludge from different sections of a wastewater treatment plant under the influence of varying operational parameters and determining experimentally the optimum operating conditions. It also involved the development of predictive rheological model based on historical data so that rheology can be used as a tool for the monitoring, control, and optimization of dewatering process.